Modification of the Association Between Frequent Aspirin Use and Ovarian Cancer Risk: A Meta-Analysis Using Individual-Level Data From Two Ovarian Cancer Consortia. Issue 11 (November 2022) - Hurwitz, Lauren M.; Townsend, Mary K.; Jordan, Susan J.; Patel, Alpa V.; Teras, Lauren R.; Lacey, James V.; Doherty, Jennifer A.; Harris, Holly R.; Goodman, Marc T.; Shvetsov, Yurii B.; Modugno, Francesmary; Moysich, Kirsten B.; et al.
Abstract : (Abstracted from J Clin Oncol 2022; doi: 10.1200/JCO.21.01900) Ovarian cancer is the deadliest gynecologic cancer because of its nonspecific symptom presentation and lack of early detection or prevention strategies. Chronic inflammation has been demonstrated to play a key role in the molecular mechanisms driving ovarian cancer.